UTILIZATION OF SOCIAL MEDIA BY DAILY CATTLE FARMERS DURING THE COVID-19 PANDEMIC: (Case Study of Rejeki Barokah Livestock Group) (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to analyzed: (1) the use of the internet and social media by dairy farmers from the Rejeki Barokah livestock group as a source of information during the Covid-19 pandemic, (2) factors that influence the utilization and use of social media by dairy farmers from the Rejeki Barokah cattle’s group as a source of information for farmers during the Covid-19 pandemic, (3) the impact of using the internet and social media by dairy farmers from the Rejeki Barokah livestock group as a source of information in Bringin Village, Wajak District, Malang Regency in January-March 2022. This research was conducted using qualitative methods. Main informants in this study was determined by purposive sampling method as many as 5 resource persons and key informants using snowball sampling as many as 7 sources. The method of collecting data is through in-depth interviews or in-depth interviews. The data analysis in this study used the Miles and Huberman data analysis technique and the validity of the data was determined by the triangulation method. Based on the results of data analysis, data obtained: (1) The use of the internet and social media is the use of Whatsapp, Facebook, Browser, and Youtube. (2) The factor of using social depends on their occupation, culture, personality, level of awareness of information, gender, age, availability of time, access, cost, information overload, and the importance of using social media. (3) The impact arising from the use of social media by members in the form of cognitive, conative, affective and psychomotor effects, the use of social media also has an impact on the knowledge of farmers and from the emergence of these impacts can also have an impact on increasing the scale of the livestock business of members Rejeki Barokah Livestock group